Pengaruh Beban Kerja dan Komitmen Organisasi Terhadap Loyalitas Karyawan pada Human Initiative Depok - Eka, Priehadi Dhasa (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to determine the Effect of Workload and Organizational Commitment on Employee Loyalty at Human Initiative Depok. This study uses a quantitative method with a sample used in this study as many as 53 respondents. The sampling technique uses saturated sample theory. Data collection uses the SPSS 26 program. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, determination coefficient analysis in hypothesis testing. The results of the study and hypothesis show that the value of the regression equation Y = 30.121 + 0.361 X1 T test obtained a t count value> t table or (2.728> 1.675) and with a p value <Sig. 0.050 or (0.050 <= 0.090). Thus H01 is rejected and Ha1 is accepted, meaning that there is no significant effect of workload on employee loyalty. While the T test obtained a t count value> t table or (3.964> 1.675) and is strengthened by a p value <Sig. 0.050 or (0.000 < 0.050). Thus H02 is rejected and Ha2 is accepted, meaning that there is a significant positive influence of organizational commitment on employee loyalty. Workload (X1) and Organizational Commitment (X2) have a significant effect simultaneously on Employee Loyalty (Y). This is evidenced by the regression equation Y = 24.789 + 0.184X1 + 0.398X2. The correlation coefficient value obtained is 0.512, meaning that it has a moderate relationship. The determination coefficient value is 0.261 or 26.1% while the remaining 73.9% is influenced by other factors. The f test obtained the Fcount value> Ftable or (8.894> 2.790) and is strengthened by the p value < Sig. 0.050 or (0.000 <0.050). Thus H03 is rejected and Ha3 is accepted.